Laser Written Glass Interposer for Fiber Coupling to Silicon Photonic Integrated Circuits - A. Desmet; A. Radosavljevic; J. Missinne; D. Van Thourhout; G. Van Steenberge (IEEE Photonics Journal, 2021)
Recent advancements in photonic-electronic integration push towards denser multichannel fiber to silicon photonic chip coupling solutions. However, current packaging schemes based on suitably polished fiber arrays do not provide sufficient scalability. Alternatively, lithographically-patterned fused silica glass interposers have been proposed, allowing for the integration of fanout waveguides between a dense array of on-chip silicon waveguides and a cleaved fiber ribbon. In this paper, we propose the use of femtosecond laser inscription for the fabrication of the fused silica glass interposer, allowing for a monolithic integration of waveguides and V-grooves for fiber alignment. The waveguides obtained by Femtosecond Laser Direct Writing (FLDW) have a propagation loss of 0.88 dB/cm at 1550 nm. The mode-field diameter is 12.8 $±$ 0.4 $μ$ m, allowing for a coupling loss of 1.24 $±$ 0.32 dB when coupling to a standard single mode optical fiber, passively aligned to the fused silica waveguide by insertion in a V-groove created by Femtosecond Laser Irradiation followed by Chemical Etching (FLICE). The average surface roughness of the etched waveguide facet is 160 $±$ 5 nm. Scattering loss when coupling to fiber is reduced by use of an index-matching adhesive for fiber fixation. A polished out-of-plane coupling mirror at an angle of 41.5 $^{° }$ injects the light into standard grating couplers, providing a quasi-planar fiber-to-chip package. The excess loss of the proposed solution is limited to 2 dB per interface, including mirror, waveguide and fiber coupling losses.